cemA homologue essential to CO2 transport in the cyanobacterium Synechocystis PCC6803. - Katoh, A (1996)
We have isolated mutants of Synechocystis PCC6803 that grew very slowly in a low-sodium medium, which is unfavorable for HCO3(-) transport, and examined two of these mutants (SC1 and SC2) for their ability to take up CO2 and HCO3(-) in the light. The CO2 transport activity of SC1 and SC2 was much lower than that of the wild type (WT), whereas there was no difference between the mutants and the WT in their activity of HCO3(-) transport. A clone containing a 3.9-kilobase-pair insert DNA that transforms both mutants to the WT phenotype was isolated from a genomic library of WT Synechocystis. Sequencing of the insert DNA in the region of mutations in SC1 and SC2 revealed an open reading frame (designated cotA), which showed significant amino-acid sequence homology to cemA encoding a protein found in the inner envelope membrane of chloroplasts. The cotA gene is present in a single copy and was not cotranscribed with any other gene(s). cotA encodes a protein of 247 amino acids containing four transmembrane domains. There was substitution of a single base in SC1 and two bases in SC2 in their cotA genes. A possible role of the cotA gene product in CO2 transport is discussed.